The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.17352/2455-815x.000039
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Eating Quality in Sensory Panelist and Instrumental Tenderness of Beef from Harar, Arsi and Bale Cattle Breeds in Oromia, Ethiopia

Abstract: Meat is one of the most nutritious animal products that humans can consume, particularly in terms of supplying high-quality protein, minerals and essential vitamins. Hence, the demand for meat is not only quantity wise, but also quality wise. The objective of this study was evaluate eating qualities of beef produced at public abattoirs from Arsi, Bale and Harar cattle breeds with semi-trained sensory panel evaluation and instrumental tenderness. To know the status of meat produced for domestic market in relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…These reports justify the possible contribution of physical exercise to a greater proportion of connective tissue, insoluble collagen, and type I fiber, which might also contribute to the relatively higher value of WBSF observed in the beef sample produced in the MCL system. The possibility of an association between draft utilization of oxen and beef quality was also suggested by Gadisa et al [28] and Tefera et al [36]. Animals exposed to long-term preslaughter stress can reduce glycogen stores at slaughter [37].…”
Section: Quality Of Beef Produced From Oxen Raised Under the Mixed Cr...mentioning
confidence: 76%
See 2 more Smart Citations
“…These reports justify the possible contribution of physical exercise to a greater proportion of connective tissue, insoluble collagen, and type I fiber, which might also contribute to the relatively higher value of WBSF observed in the beef sample produced in the MCL system. The possibility of an association between draft utilization of oxen and beef quality was also suggested by Gadisa et al [28] and Tefera et al [36]. Animals exposed to long-term preslaughter stress can reduce glycogen stores at slaughter [37].…”
Section: Quality Of Beef Produced From Oxen Raised Under the Mixed Cr...mentioning
confidence: 76%
“…Mume [26] reported a high level of ultimate pH in beef from cattle reared in the MCL system. Similarly, Gadisa et al [28] reported a relatively higher ultimate pH for beef from oxen raised in the MCL system. Birhanu [38] reported high levels of DFD in beef from bulls reared in the MCL system.…”
Section: Quality Of Beef Produced From Oxen Raised Under the Mixed Cr...mentioning
confidence: 86%
See 1 more Smart Citation
“…Few studies were conducted to evaluate qualities of beef in Ethiopia and reported difference in instrumental tenderness and sensory characteristics of beef from Arsi, Bale, Boran and Harar cattle breeds [11] [12]. However, the cause for the difference in eating quality was not investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies were conducted to evaluate the quality of beef produced from local cattle breeds using instrumental methods and scanty research was available using sensory panel testing. Instrumental method using WBSF device is the best option to compare the quality across age and breeds as sensory panel testing is subjective between individuals involved in panel testing [7]. Based on these gaps, this research was designed with the objective to evaluate the eating quality of beef from Arsi, Borana, and Harar cattle breeds based on instrumental tenderness and sensory panel testing.…”
Section: Introductionmentioning
confidence: 99%